ISOLATION OF QUERCETIN FROM FLOWER PETALS, ESTIMATION OF TOTAL PHENOLIC, TOTAL FLAVONOID AND ANTIOXIDANT ACTIVITY OF THE DIFFERENT PARTS OF RHODODENDRON ARBOREUM SMITH - Bhandari, Laxman; Rajbhandari, Meena (Scientific World, 2015)
The flowers of Rhododendron arboreum Smith is a source of polyphenolic compounds. A flavonol, quercetin, was isolated from ethyl acetate fraction of the methanol extract of flower petals of R. arboreum by repeated Sephadex LH-20 column chromatography. Isolated quercetin was characterized by comparing melting point, Rf values, UV and IR spectra with authentic quercetin. The isolated quercetin was used as a standard for the estimation of total flavonoids. Total phenolic and total flavonoid content in different parts of R. arboreum was carried out spectrophotometrically using Folin-Ciocalteu reagent and Aluminium chloride reagent respectively. Gallic acid and quercetin were used as standard for the construction of calibration curve of phenolic and flavonoid respectively. The results showed that the highest total phenolic content was detected in the 70% acetone extract of the flowers (600 mg GAE/g extract) and petals (600 mg GAE/g extract) and the lowest amount was detected in methanol extract of stem (188 mg GAE/g extract). Similarly, the highest total flavonoid was detected in the 70% acetone extract of the twigs (170 mg QE/g extract) and the lowest amount was detected in the methanol extract of stem (45 mg QE/g extract). The antioxidant activity of the methanol extracts obtained from different parts of R. arboreum was determined by 2, 2- diphenyl-1-picryl hydrazyl (DPPH) assay and the radical scavenging activity (IC50) was calculated. The highest free radical scavenging effect was observed in leaves with IC50=8.34 ?g/ml and lowest was observed in stem with IC50=67.83 ?g/ml. The IC50 values, total phenolic and total flavonoid content (correlation coefficient R2= 0.923 for phenolic, R2= 0.965 for flavonoid) were correlated which showed strong correlation indicating that the major components responsible for antioxidant activity is phenolics. The highest the phenolic content, the lowest the IC50 value observed. The result indicated that R. arboreum is a rich source of high value polyphenols as natural antioxidant to use in preventive medicine as well as in food and pharmaceutical industry. Scientific World, Vol. 12, No. 12, September 2014, page 34-40